First record of the fig wasp genus Diaziella Grandi (Hymenoptera: Chalcidoidea: Pteromalidae: Sycoecinae) from the Asian mainland with description of two new species from China - van Noort, Simon; Peng, Yan-Qiong; Rasplus, Jean-Y (Zootaxa, 2006)
Diaziella bizarrea van Noort & Rasplus sp. nov. is described from specimens reared from Ficus glaberrima and Diaziella yangi van Noort & Rasplus sp. nov. is described from specimens reared from Ficus curtipes in Xishuangbanna, China. Together with a new record of Diaziella macroptera Grandi from Thailand this is the first time the genus has been recorded from the Asian mainland. Previously the twelve described species of Diaziella were known from the islands of Borneo, Java, Sumatra, Sulawesi and the Philippines. Images are provided for both sexes of the two new species and for the female of D. macroptera. A key is included to all described species of Diaziella. An online key is available at: http://www.figweb.org/Fig_wasps/Pteromalidae/Sycoecinae/Key/ Diaziella.htm. Host relationships and biology are discussed.